COLOR REMOVAL FROM DYE EFFLUENT BY USING COAGULATION TECHNIQUE - ASHOK KUMAR POPURI,; BANGARAIAH PAGALA, (International Journal of Pharma and Bio Sciences, 2013)
Dyes are coloring compounds being extensively used in almost all industries and the indiscriminate disposal of dye wastewater poses one of the major problems on the environment. This effluent containing a variety of contaminants viz. Nature of acidic, caustic, dissolved solids and toxic compounds like organic, inorganic or heavy metallic. The micro toxins are developed due to coloring agents by forming chelating under suitable chemical environment. The objective of the present work is to investigate the effectiveness of chemical treatment on removal of color of simulated acid dye solutions. Two dye stuffs one belongs to acid group and other vat dye were employed and batch tests were conducted with three coagulants (Alum, Ferric chloride & Aluminium chloride) to access feasibility and also to study the optimum coagulant dosage . The study clearly indicates that Napthal-I responds effectively to both Alum & AlCl3. Napthal-II responds effectively to Alum. Vat dye is moderately responded to FeSO4.7H2O. The removal probably due to physicochemical mechanism of coagulation and flocculation and/or chelating complexation type reactions. A perusal of color removal data suggest that the color mechanism is predominately physicochemical coagulation especially at alkaline PH ranges, presumable due to absorption on to hydroxide flocs, and color removal at lower PH ranges may be either due to physicochemical coagulation or chelation complex formation reactions. The study clearly indicates that optimum PH system conditions, there is significant reduction in the chemical dosage requirements and in some cases a further increase in color removal. From the above studies it may be concluded that some of the Acid & Vat dye stuffs are amenable for their color removal and shows positive response for treatment by chemical process using various coagulants.